The Hero and his Values - Mikučionis, Ugnius (Scandinavistica Vilnensis, 2019)
In this article, I argue that the portrayals of Sigurðr Fáfnisbani as a hero that emerge from the narratives about the slaying of the dragon in the Prose Edda and in the Saga of the Volsungs are rather different. A hero’s essence is not only about what actions the hero performs or what physical qualities the hero possesses, but also about what choices he makes and what values he adheres to. Therefore, one has to investigate why Sigurðr chose to agree to slay Fáfnir in order to be able to judge how heroic this deed was – or was not. A comparative analysis of the two source texts shows that while the main motivating factor for Sigurðr in the Prose Edda version of the narrative is the prospect of gaining Fáfnir’s treasure, the version contained in the Saga of the Volsungs gives a completely different picture. Here, the main motivation arises from Sigurðr’s own desire to avenge those who had killed his father, Sigmundr. In order to be able to wreak his vengeance, Sigurðr needs a suitable weapon, a sword without equal. Since Reginn is extraordinarily zealous in inciting Sigurðr to slay Fáfnir, Sigurðr promises to do so in exchange for a sword that Reginn – who is a smith with supernatural, dwarf-like competences – has to fashion using all his skill and effort. Additionally, avenging the injustice suffered by Reginn seems morally right, and is compatible with Sigurðr’s plans. The prospect of acquiring a hoard of gold may have contributed to his resolution, but in the Saga of the Volsungs it is not the main motivating factor for Sigurðr.
Keywords: Hero; choices; values; duty; honour; justice; vengeance; actantial model; Sigurðr; Fáfnir; Reginn; Edda; Snorri Sturluson; Vǫlsunga saga; Algirdas Julien Greimas